Association of the Lactase Persistence Haplotype Block With Disease Risk in Populations of European Descent - Joslin, Shannon E. K.; Durbin-Johnson, Blythe P.; Britton, Monica; Settles, Matthew L.; Korf, Ian; Lemay, Danielle G. (Frontiers in Genetics, 2020)
Among people of European descent, the ability to digest lactose into adulthood arose via strong positive selection of a highly advantageous allele encompassing the lactase gene. Lactose-tolerant and intolerant individuals may have different disease risks due to the shared genetics of their haplotype block. Therefore, the overall objective of the study was to assess the genetic association of the lactase persistence haplotype to disease risk. Using data from the 1000Genomes project, we estimated the size of the lactase persistence haplotype block to be 1.9 Mbp containing up to 9 protein-coding genes and a microRNA. Based on the function of the genes and microRNA, we studied health phenotypes likely to be impacted by the lactase persistence allele: prostate cancer status, cardiovascular disease status, and bone mineral density. We used summary statistics from large genome-wide metanalyses—32,965 bone mineral density, 140,306 prostate cancer and 184,305 coronary artery disease subjects—to evaluate whether the lactase persistence allele was associated with these disease phenotypes. Despite the fact that previous work demonstrated that the lactase persistence haplotype block harbors increased deleterious mutations, these results suggest little effect on the studied disease phenotypes.